Research Notes: Correcting Turnover Statistics for Comparative Analysis - Steel, Robert P.; Shane, Guy S.; Griffeth, Rodger W. (Academy of Management Journal, 1990)
Variability in turnover base rates may bias the results of comparative analyses in research on turnover. This article illustrates statistical corrections to turnover correlations based on range restriction formulas. Comparative analysis using corrected statistics seeks to facilitate the process of unbiased comparative inference.